2023
DOI: 10.15252/emmm.202216225
|View full text |Cite
|
Sign up to set email alerts
|

Targeting gut dysbiosis against inflammation and impaired autophagy in Duchenne muscular dystrophy

Abstract: Nothing is known about the potential implication of gut microbiota in skeletal muscle disorders. Here, we provide evidence that fecal microbiota composition along with circulating levels of shortchain fatty acids (SCFAs) and related metabolites are altered in the mdx mouse model of Duchenne muscular dystrophy (DMD) compared with healthy controls. Supplementation with sodium butyrate (NaB) in mdx mice rescued muscle strength and autophagy, and prevented inflammation associated with excessive endocannabinoid sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 88 publications
2
26
0
Order By: Relevance
“…Interestingly, among the microbial metabolites that differed between wildtype and mdx groups, SCFA and key precursors in the biosynthesis pathway of SCFA were found to be significantly reduced in the plasma. Notably, in addition to reversing deficits in locomotor activity, SCFA levels, muscle autophagy, and inflammation, Kalkan et al show that DFZ treatment induced a remarkable increase in the concentration of SCFA, butyrate, known to have beneficial roles including anti‐inflammatory and immunomodulatory properties (Fernandes et al , 2020; Kalkan et al , 2023).…”
Section: Figure the Gut‐muscle Axismentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, among the microbial metabolites that differed between wildtype and mdx groups, SCFA and key precursors in the biosynthesis pathway of SCFA were found to be significantly reduced in the plasma. Notably, in addition to reversing deficits in locomotor activity, SCFA levels, muscle autophagy, and inflammation, Kalkan et al show that DFZ treatment induced a remarkable increase in the concentration of SCFA, butyrate, known to have beneficial roles including anti‐inflammatory and immunomodulatory properties (Fernandes et al , 2020; Kalkan et al , 2023).…”
Section: Figure the Gut‐muscle Axismentioning
confidence: 99%
“…Given that gastrointestinal and metabolic issues are common in patients with DMD, these two studies unfold the possibility of using gut microbiota metabolite intervention strategies for managing or reversing DMD symptoms (Farini et al , 2022; Kalkan et al , 2023). If the use of SCFA or molecules stimulating the production of SCFA can be shown to have beneficial effects in patients with DMD, they may increase the arsenal of therapies that may slow down the progression of DMD and complement steroid treatment.…”
Section: Figure the Gut‐muscle Axismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Proteobacteria bloomed and Bacteroidetes declined in the presence of NAEs. Kalkan et al 8 recently showed that in mdx mice, a model of Duchenne’s Muscular Dystrophy (DMD), the disease is associated with a significant alteration in gut microbiota composition, which results in the reduction of the plasma levels of SCFAs. Administration of one such molecule, sodium butyrate (NaB), rescued impaired muscle strength and autophagy, and prevented inflammation, all of which were due to excessive eCB signaling at CB1 receptors.…”
Section: The Gμbiome–ecbome Axis In Peripheral Inflammation and Brain...mentioning
confidence: 99%
“…NaB simultaneously reduced anandamide and CB1 receptor expression levels in mdx mouse skeletal muscle, and, in both murine and DMD human myoblasts, it exerted anti-inflammatory effects, promoted autophagy, and prevented excessive CB1 signaling by restoring normal levels of microRNAs that suppress CB1 expression. 8 …”
Section: The Gμbiome–ecbome Axis In Peripheral Inflammation and Brain...mentioning
confidence: 99%